Faktor yang Mempengaruhi Keputusan Transfer Pricing pada Perusahaan Sektor Consumer Non-Cyclicals - Sari, Natasya Permata; Veny, Veny (Universitas Prasetiya Mulya, 2023)
The study aimed to determine the impact of Tax Minimization, Company Size, Debt Covenant, and Profitability on the Transfer Pricing decision in non-cyclical companies. The theoretical framework supporting this study is the agency theory. The study used a quantitative causal comparative approach with a population and sample of non-cyclical companies listed on the Indonesia Stock Exchange (BEI) from 2018 to 2022. The sample was obtained based on predefined criteria. The analysis in this study included descriptive statistics, classical assumption tests, and linear regression analysis, which was processed using IBM SPSS version 25. Based on the test results, it was found that: (1) Tax Minimization had a significant negative impact on transfer pricing; (2) Company Size had not a significant positive impact on transfer pricing; (3) Debt Covenant had a significant negative impact on transfer pricing; (4) Profitability had not a significant negative impact on transfer pricing.